Impact of Fontan Fenestration on Long‐Term Outcomes: A Propensity Score–Matched Analysis - Michael Daley; Edward Buratto; Gregory King; Leeanne Grigg; Ajay Iyengar; Nelson Alphonso; Andrew Bullock; David S. Celermajer; Julian Ayer; Terry Robertson; Yves d’Udekem; Igor E. Konstantinov (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The long‐term impact of fenestration at the time of Fontan operation remains unclear. We aimed to review the early and long‐term impact of Fontan fenestration in the Australia and New Zealand cohort. Methods and Results We reviewed 1443 patients (621 fenestrated, 822 nonfenestrated) from the Australia and New Zealand Fontan registry. Data were collected on preoperative demographics, operative details, and follow‐up. Propensity‐score matching was performed to account for the various preoperative and operative differences and risk factors. Primary outcomes were survival and freedom from failure. Median follow‐up was 10.6 years. After propensity‐score matching (407 matched pairs), there was no difference in survival (87% versus 90% at 20 years; P=0.16) or freedom from failure (73% versus 80% at 20 years; P=0.10) between patients with and without fenestration, respectively. Although patients with fenestration had longer bypass and cross‐clamp times (P<0.001), there was no difference in hospital length of stay or prolonged pleural effusions (P=0.80 and P=0.46, respectively). Freedom from systemic and Fontan circuit thromboembolism was higher in the nonfenestrated group (89%; 95% CI, 88%–95%) than the fenestrated group (84%; 95% CI, 77%–89%; P=0.03). There was no difference in incidence of plastic bronchitis, protein‐losing enteropathy, New York Heart Association Class III/IV symptoms, or Fontan takedown. Conclusions In the propensity score–matched analysis we have demonstrated no difference in long‐term survival or freedom from Fontan failure in patients with and without fenestration. There was a higher incidence of long‐term thromboembolic events in patients with fenestration. Overall, it appears that fenestration in Fontan circulation does not bring long‐term benefits.